Biological inspired autonomously secure mechanism for wireless sensor networks - Saleem, Kashif (Taylor & Francis Group, 2010)
Wireless communication plays an important role in these days in the sector of telecommunication and has huge importance for future research. There has been an exponential growth in wireless communication due to the development of different devices and applications. In addition, there is an explosive increase in integration and convergence of different heterogonous wireless networks to ensure effective and efficient communication. These technologies primarily includes Wireless Wide Area Networks (WWANs), Wireless Local Area Networks (WLANs), Wireless Personal Area Net-works (WPANs), and the Internet. The cellular networks can be classified under the WWAN, Blue-tooth, and Ultrawide Bands classified as WPANs, and finally the WLANs and High-Performance Radio Local Area Networks (HiperLANs) belongs to the WLAN class.